ORGANIZATIONAL CITIZENSHIP BEHAVIORS AND SOCIAL SUPPORT AT WORK: SCENARIO ANALYSIS THROUGH SYSTEN DYNAMIC - Costa, Gabrielle Loureiro de Ávila; Gomes, Tarízi Cioccari; de Oliveira, Bruna Brandt; Rodrigues, Glauco Oliveira; Simonetto, Eugênio de Oliveira; Estivalete, Vania de Fátima Barros (Pensamento & Realidade, 2022)
This study aimed to present the development and validation of a simulation model that allows the People Management area to evaluate and analyze scenarios based on Organizational Citizenship Behaviors and Social Support at Work. For this, we considered the perspective of IT knowledge workers who work in companies from different states of Brazil. To achieve this goal, the simulation model was elaborated and its possible analysis performed with the system dymanics. The 'current scenario' was based on the study by Costa (2019) who used the Dekas et al. (2013), validated by Andrade (2017) for the Brazilian context and the Siqueira and Gomide Jr Social Work Support Scale (2008). As a result it stands out that Aid had a small growth in the optimistic scenario, compared to the other dimensions, Civic Virtue and Voice. On the other hand, the three dimensions showed large decreases in the pessimistic scenario. It is also noted that the median scenario, in the five years of simulation, increased from 4.04 to 4.12, while the optimistic scenario showed a great increase, from 4.04, value of year 0, reaching 4.91 in year 5.